Políticas de acceso al financiamiento del micro, pequeño y mediano productor en las cadenas globales de mercancías: crédito e IED - Díaz Porras, Rafael Antonio (2016)
This article connects theory and global commodity chain concepts to traditional financing theory in order to propuse changes in areas such as property rights, comercial legislation, financial legislation, and supervisión that would allow financial institutions to créate non-conventional financial products for small scale rural entrepreneurs, organized groups of processors, and exporters to have access to finance or improve the conditions in which they receive it and thus ensure that they are integrated to the global commodity chain on a sustainable manner. Although both approaches are treated independently in literature, related publications were analyzed to determine which áreas would support the proposal of having access to finance from the point of view  of  global  commodity  chains  and  of  having this  proposal  become a  new  banking  technology  paradigm for financial agents. This paper analyzes the  structure and financing flows between chain  agents  and  national  and  international financial  agents,  as  well  as  the  role  of  foreign  direct  investment in the financing of global commodity chains. The proposal for financial  agents to create  new  financing  inst ruments  in  the  context  of  global  commodity  chains  is  built  as  a  result  of the  analysis  of  the  characteristics  of  chains,  producer  agents  and  commercial  and  financial  contracts,  which  would  guarantee r ecovery of the resources provided.